Learning model focused on STEM (knowledge, technology, engineering and mathematics) to achieve excellence in the field education in the Turkic-speaking world of the 21st century (Journal of Pedagogical Inventions and Practices, 2024)
In this article, the author talks about the main tasks of the STEM approach, which is currently being implemented at the state level in countries focused on the development of their scientific and technical elite